(untitled) (Collection of scientific works «Modern structures of metal and wood», 2020)
Framed multi-storey wooden residential construction is developing very rapidly in many countries around the world. The use of wooden infill beams made of wooden glued beams and OSB (oriental strand board) increases the efficiency of design solutions. Especial difficult in the design and manufacture of beam structures in multi-storey framed houses are the beam-column joints, which can be hinged or supple. Preferably, these nodes are considered supple, which ensures the spatial operation of the frame and reduces its deformability against the hinges. As a rule, nodes are executed with steel elements which connect beams to columns by means of bolts and nails. The following constructive decision of a frame node is offered: a rectangular glued column and a crossbar in the form of an I-beam with an OSB-wall and regiments from a bar strengthened by glued wood in supporting zones. Support zones of crossbars are made of continuous rectangular section of a glued bar. For support of crossbars on a column the head with projecting beams from sheet steel up to 4 mm thick, with apertures for fastening is put on. The overhanging length corresponds to the width of the support zones of the crossbars. After fixing the crossbars to the projecting beam, the support area of he column of the upper floor is connected to the upper shelf of the crossbars with a fastening element in the form of a corner. The wall of the projecting beam is attached to the column, the projecting beam shelf is attached to the bottom shelf of the beam. The vertical walls of the projecting beam on both sides are attached to the wall of the support zone of the beam. To analyze the stress-strain distribution of the I-beam in the software complex "LIRA-SAPR" was developed a spatial computer model of the node. The stress-strain distribution of the beam was analyzed by the fields of displacements and stresses, as well as by the deformations of the structure. The research results allow us to conclude about the structural reliability of the proposed node solution.